Does hydroxyprogesterone caproate injection alter second trimester screening markers and neonatal outcomes? - Madendağ, Yusuf; Çöl Madendağ, İlknur (Journal of Surgery and Medicine, 2019)
Aim: In the second trimester, biochemically evaluating maternal serum markers such as alpha-fetoprotein (AFP), unconjugated estriol (uE3), and human chorionic gonadotropin (hCG) may be performed as prenatal screening for neural tube defects (NTDs) and fetal aneuploidy and anomalies. We evaluated whether supplementation of 17-hydroxyprogesteronecaproate (17OHPC) in the second trimester can effect these markers. In addition, we evaluated pregnancy outcomes in pregnant women using 17OHPC. Methods: This case control study included 1275 pregnant women between December 2014 and March 2018. The progesterone (study) group included women with a previous preterm birth and cervical length >25 mm. The control group included healthy pregnant women with a cervical length >25 mm and no previous preterm birth. Maternal age, body mass index (BMI) at the time of screening, gestational age at the time of screening, levels of maternal serum AFP, uE3, and hCG, fetal sex, fetal birth weight, Apgar score 5th minute <7, and admission to the neonatal intensive care unit (NICU) were evaluated. Results: There was no statistically significant difference for maternal age, BMI, gestational age, fetal sex, fetal birth weight, Apgar score 5th minute <7, and admission to the NICU. The mean maternal serum uE3 and AFP levels were significantly less in the study group than in control group (P=0.008 and P=0.046, respectively). However, the mean maternal serum hCG levels were significantly higher in the study (P=0.033). Conclusions: Second trimester screening tests for fetal aneuploidy and NTDs can give incorrect results in pregnant women using 17OHPC. These incorrect results may cause misdiagnosis and over-management. New threshold values for these markers in pregnant women using 17OHPC should be identified.